Uporništvo ženskih likov v prozi Zofke Kveder - Borovnik, Silvija (Jezik in slovstvo, 2007)
Zofka Kveder is still considered the first Slovene writer-intellectual, who entered the Slovene literary scene at the turn of the 19th into the 20th century. Recent literary-historical studies (by Silvija Borovnik, Zvonko Kovač, Katja Mihurko Poniž) point out that at the time when engagement in literature was a male domain, not to say almost privilege, she was a bold, independent and innovative personality. Resolutely determined to find her own place in the professional world, though there was hardly any place left for women, she left home, which did not provide any safety or warmth, and first found employment. Then, without any help from her parents, she sought education in Trieste, and later at the universities in Zurich and Prague. Alongside her studies she began to develop her writing. When a few years ago I took a serious interest in literature, written by Slovene female authors, I came to realise that all beginnings and all new paths, developed by female writers and poets in the 20th century, point to Zofka Kveder. Other literary theoreticians also point out that it was Zofka Kveder herself who succeeded in gaining recognition in the Slovene, Czech and Croatian literary worlds by writing and publishing in four languages.
Keywords: Kveder; Kveder, Zofka; literarne študije; Slovene literature; slovenska književnost; uporništvo; woman; ženske